101k views
5 votes
Combine like terms in the expression below and select the answer choice that is equivalent. 5x + 2x2 - 3 + x - 4x2

2 Answers

7 votes

Answer:

6x-7

Explanation:

5x + x = 6x

______________

2 x 2 - 3 = 4 - 3 = 1

1 - 4 x 2 = 1 - 8 = -7

______________

6x - 7

User Helgi
by
5.4k points
3 votes

Let's simplify step-by-step.

5x + 2x^2 − 3 + x − 4x^2

=5x + 2x^2 + −3 + x + −4x^2

Combine Like Terms:

=5x + 2x^2 + −3 + x + −4x^2

=(2x^2 + −4x^2)+(5x + x) + (−3)

=−2x^2+ 6x + −3

User Mayous
by
5.2k points